2014
DOI: 10.1017/s0033291714001226
|View full text |Cite
|
Sign up to set email alerts
|

Do genetic risk scores for body mass index predict risk of phobic anxiety? Evidence for a shared genetic risk factor

Abstract: Background Obesity and anxiety are often linked but the direction of effects is not clear. Methods Using genetic instrumental variable (IV) analyses in a sample of 5911 female participants from the Nurses´ Health Study (NHS, initiated in 1976) and 3697 male participants from the Health Professional Follow-up Study (HPFS, initiated in 1986), we aim to determine whether obesity increases symptoms of phobic anxiety. FTO, MC4R, and a genetic risk score (GRS) based on 32 single nucleotide polymorphisms that signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…The prevalence of anxiety has been shown to be higher in obese compared with non-obese people [3944] and higher in both underweight and overweight/obese people compared with those of normal weight [45]. The few instrumental variable studies estimating the causal effect of BMI on anxiety that have been performed to date (one specifically looking at phobic anxiety [46] and the other using an anxiety measure defined using the Hospital Anxiety and Depression Scale [HADS] 50 ), did not find evidence of a causal effect, although this may be due to insufficient statistical power [46,47]. Some previous MR studies using a BMI genetic risk score provided evidence that an increase in BMI adversely affects risk of depression symptoms [48] and major depressive disorder [49] while others found little evidence [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anxiety has been shown to be higher in obese compared with non-obese people [3944] and higher in both underweight and overweight/obese people compared with those of normal weight [45]. The few instrumental variable studies estimating the causal effect of BMI on anxiety that have been performed to date (one specifically looking at phobic anxiety [46] and the other using an anxiety measure defined using the Hospital Anxiety and Depression Scale [HADS] 50 ), did not find evidence of a causal effect, although this may be due to insufficient statistical power [46,47]. Some previous MR studies using a BMI genetic risk score provided evidence that an increase in BMI adversely affects risk of depression symptoms [48] and major depressive disorder [49] while others found little evidence [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Educational attainment was constructed as a categorical variable with four levels: less than high school education (reference group), high school or GED completed, some college, and college completed. We also account for residual population stratification by including the first four genetic principal components-derived eigenvectors, a technique used in prior work (Chang and others 2014; Walter and others 2015). …”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of anxiety has been shown to be higher in obese compared with non-obese people 4347 , although Vainik et al found no correlation between BMI and neuroticism 48 . The few instrumental variable studies estimating the causal effect of BMI on anxiety that have been performed to date (one specifically looking at phobic anxiety 49 and the other using an anxiety measure defined using the Hospital Anxiety and Depression Scale (HADS) 50 ), did not find evidence of a causal effect, although this may be due to insufficient statistical power 49,50 . Two recent MR studies provided evidence that an increase in BMI adversely affects risk of depression symptoms 51 and major depressive disorder 52 .…”
Section: Discussionmentioning
confidence: 99%